2021
DOI: 10.1051/e3sconf/202123201024
|View full text |Cite
|
Sign up to set email alerts
|

Community Participation in the Development of Urban Farming in Yogyakarta City

Abstract: The optimal yard utilization would support the family’s food independence a well-managed yard will provide benefits in improving family food self-sufficiency, nutrition, increasing family income, and making a beautiful, picturesque, and comfortable home environment. Efforts to build family food security in urban areas can be carried out through yard utilization on a narrow land. This study aims to determine the urban yard utilization and the members’ participation in it. The research was conducted in Bausasran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 11 publications
0
3
0
2
Order By: Relevance
“…Urban farming requires a good collaboration built from each individual or Women Farmers Group member as a pioneer involved. Activities in each urban farming activity invite the surrounding community to participate by utilizing the potential of the yard in each house to foster public interest in the practice of urban farming directly [30]. Moreover, urban farming impacts social life, such as reducing poverty and crime [31], and create meaningful job opportunities [32].…”
Section: Resultsmentioning
confidence: 99%
“…Urban farming requires a good collaboration built from each individual or Women Farmers Group member as a pioneer involved. Activities in each urban farming activity invite the surrounding community to participate by utilizing the potential of the yard in each house to foster public interest in the practice of urban farming directly [30]. Moreover, urban farming impacts social life, such as reducing poverty and crime [31], and create meaningful job opportunities [32].…”
Section: Resultsmentioning
confidence: 99%
“…These sites can be effectively utilized for urban farming to enhance efficiency and sustainability. A case study conducted by Wulandari et al [44]. in Yogyakarta City showed that the community has taken proactive steps by forming an organization known as 'Kampung Sayur Bausasran.'…”
Section: Community Engagement and Well-beingmentioning
confidence: 99%
“…Prinsip pemanfaatan lahan pekarangan dari aspek estetika adalah menjadikan pekarangan lebih indah, lebih nyaman, dan berkualitas. Budidaya tanaman harus ditata atau diletakkan sedemikian rupa di lahan pekarangan rumah (Wulandari et al, 2021) .…”
Section: Pendahuluanunclassified